Diagnostic assessment of patients with Meniere's disease through caloric testing and the video-head-impulse test - Oliveira,Lívia Noleto de Rezende (2021)
Abstract Introduction Meniere's disease is a labyrinth disease that usually presents with episodes of spontaneous vertigo associated with sensorineural hearing loss, tinnitus and ipsi- and unilateral aural fullness in most cases. Vestibular function tests, video-head-impulse test and the caloric test, are not specific for diagnosis of the disease, but may show alterations that help to evaluate the functional impairment. Objective To describe the results obtained at the caloric test and video-head-impulse test in patients with definite Meniere's disease and compare them between symptomatic, asymptomatic ears and those of the control group. Methods Cross-sectional and observational study including patients with definite Meniere's disease diagnosed according to the Bárány Society criteria (2015) and healthy individuals (control group) undergoing caloric test and video-head-impulse test. All subjects were assessed by neurotological anamnesis and audiological evaluation (pure-tone, vocal and immittance audiometry) to characterize the sample. The findings obtained at the caloric test and video-head-impulse test were described and compared between the symptomatic and asymptomatic ears of patients with Meniere's disease and those of the control group. Results Thirty-two patients with definite Meniere's disease were evaluated, with a mean age of 45.7 years, mostly females (68.8%) and unilateral disease. The control group consisted of 20 healthy individuals, with a mean age of 44.7 years, mostly females (70.0%). The groups were homogeneous in relation to age and gender. The patients' main complaint was vertigo (71.9%), and most patients had more than six episodes in the last six months (71.9%). Moderate sensorineural hearing loss was present in 38.5% of patients. The prevalence of hyporeflexia at the caloric test was higher in symptomatic (56.4%) and asymptomatic (36%) ears of patients with Meniere's disease compared to the ears of control subjects (7.5%), p < 0.001 and p = 0.004, respectively. Video-head-impulse test alterations in the lateral semicircular canals were more frequent in the symptomatic ears of patients with Meniere's disease than in the ears of control subjects (p = 0.026). Conclusion Most patients with definite Meniere's disease showed hyporeflexia at the caloric test and video-head-impulse test with normal function in the symptomatic ear. Vestibular hyporeflexia at the caloric test was more frequent in the symptomatic and asymptomatic ears of patients with Meniere's disease than in the control group. The video-head-impulse test showed more alterations in the lateral semicircular canals.